2015
DOI: 10.1002/anie.201503312
|View full text |Cite
|
Sign up to set email alerts
|

Drug Pharmacokinetics Determined by Real‐Time Analysis of Mouse Breath

Abstract: Noninvasive, real-time pharmacokinetic (PK) monitoring of ketamine, propofol, and valproic acid, and their metabolites was achieved in mice, using secondary electrospray ionization and high-resolution mass spectrometry. The PK profile of a drug influences its efficacy and toxicity because it determines exposure time and levels. The antidepressant and anaesthetic ketamine (Ket) and four Ket metabolites were studied in detail and their PK was simultaneously determined following application of different sub-anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 29 publications
1
52
0
1
Order By: Relevance
“…We have recently shown that this technique could be used to investigate the in vivo pharmacokinetics of injected drugs in mice [42]. To further illustrate the capabilities of the optimized ionizer developed here, we tested its performance towards vapors of common drugs: Melatonin, Propofol, Acetaminophen, Pentobarbital and Midazolam.…”
Section: Detection Of Drugsmentioning
confidence: 99%
“…We have recently shown that this technique could be used to investigate the in vivo pharmacokinetics of injected drugs in mice [42]. To further illustrate the capabilities of the optimized ionizer developed here, we tested its performance towards vapors of common drugs: Melatonin, Propofol, Acetaminophen, Pentobarbital and Midazolam.…”
Section: Detection Of Drugsmentioning
confidence: 99%
“…Recently, we have shown that secondary electrospray ionization (SESI) 7 coupled with high resolution mass spectrometry (HRMS) provides sufficient sensitivity and selectivity to track in vivo and in real time the metabolism of drugs in mice breath, which correlate with blood levels. 8 . The proposed method enables capturing pharmacokinetic profiles of injected drugs in real time with a time resolution of 10 s from a single mouse in a comparably stressless procedure (Fig.…”
mentioning
confidence: 99%
“…The time-to-peak for this particular dose was found to be around 25-30 min, which is fully consistent with our previous results. 8 . In contrast, however, a clear difference in ketamine metabolism was observed.…”
mentioning
confidence: 99%
“…In this sense, breath analysis is gaining attention as a novel technique for clinical purposes such as diagnostics (11 ) and pharmacokinetics (12 ). Breath analysis can detect differences between individual "breathprints" which are reasonably stable over time (13 ), can be used to follow diurnal metabolic patterns (14,15 ), and is capable of quantifying hitherto unknown compounds in human breath (16,17 ).…”
mentioning
confidence: 99%